Cascade processing of softwood bark with hot water extraction, pyrolysis and anaerobic digestion. (November 2019) - Rasi, Saija; Kilpeläinen, Petri; Rasa, Kimmo; Korpinen, Risto; Raitanen, Jan-Erik; Vainio, Markku; Kitunen, Veikko; Pulkkinen, Henni; Jyske, Tuula
Highlights: Softwood bark can be refined into valuable compounds. HWE, pyrolysis and AD were combined as cascade process. With cascade processing, no waste streams were produced. The most important development schemes were defined. Abstract: A process model based on hot water extraction (HWE), slow pyrolysis and anaerobic digestion (AD) were used for pine and spruce bark utilisation. First tannins (32 mg/g and 11.8 mg/g, respectively) and polyphenols were recovered via HWE. Then, the residue was pyrolysed to produce biochar (marketable quality), gas (energy source) and liquid fractions. The liquid fraction was further separated into aqueous acidic fraction and to tar fraction. Bark, extracted bark residue and acidic liquid fraction from pyrolysis were treated in AD to produce biomethane and digestate. The methane yields from pine and spruce bark and extracted bark residue were low (from 42 to 96 mLCH4/gVSadded) and showed only small differences. In conclusion, cascade processing can improve the performance of subsequent single processes and utilise biomass sources with higher efficiency. The best processing chain may vary in different cases and the overall energy balance of processing needs further research.